Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Liu, Fang (Zhejiang University Press, 2013)

(untitled)
The aim of this study was to understand the characteristics of blood pressure (BP) variability in subjects with diabetic nephropathy (DN), and identify the probable predictors affecting BP variability. Fifty-one chronic kidney disease (CKD)-hypertensive patients without diabetes (NDN group) and sixty type 2 diabetic patients with overt DN (DN group) were enrolled in this study. The values of short-term BP variability were obtained from 24 h ambulatory BP monitoring (ABPM). Variance analysis or nonparametric analysis revealed that 24-h systolic BP variability and nighttime systolic BP variability of the DN group were significantly higher than those of the NDN group [(12.23±3.66) vs. (10.74±3.83) mmHg, P<0.05; (11.23±4.82) vs. (9.48±3.69) mmHg, P<0.05]. Then the patients of the DN group were divided into two groups according to glycated hemoglobin (HbA1c) level: Group A (HbA1c<7%) and Group B (HbA1c≥7%), and the t-test showed that patients in Group B had larger 24-h diastolic, daytime diastolic, and nighttime systolic/diastolic BP variability compared with Group A. In the DN group, partial correlation analysis revealed that HbA1c exhibited a strong association with 24-h diastolic, daytime diastolic, nighttime systolic and diastolic BP variability (P<0.001, P<0.001, P<0.05, and P<0.001, respectively). Taken together, larger short-term BP variability was detected in hypertensive type 2 diabetic patients with overt nephropathy and renal insufficiency. It may imply that the optimal BP variability level could benefit from a better glycaemic control.